Calcium-Mediated Biophysical Binding of Cryptosporidium parvum Oocysts to Surfaces Is Sensitive to Oocyst Age - Sarkhosh, Tooba (Appl Environ Microbiol, 2019)
Cryptosporidium parvum causes potentially life-threatening gastrointestinal disease in humans and may not be effectively removed from drinking water via conventional methods. Prior research has shown that environmental biofilms immobilize oocysts from the water column, but the biophysical mechanisms driving this attraction are still under investigation. This study investigates the affinity of C. parvum oocysts to silanized surfaces. Surfaces were prepared with hydroxyl, amine, and carboxyl moieties. Binding forces between the oocysts and these engineered substrates were analyzed, with and without divalent ions, using atomic force microscopy. Binding forces were measured over several weeks to investigate the influence of age on adhesion. C. parvum oocysts bind most strongly to carboxylic acid functional groups, with rupture forces greater than that required to break noncovalent molecular bonds, regardless of oocyst age. This adhesion is shown to be due to divalent cation bridging mechanisms. In addition, the binding strength increases over a 5-week period as the oocysts age, followed by a decrease in the binding strength, which may be related to structural or biochemical changes in the outer wall-bound glycosylated proteins. This study sheds new light on the biochemical parameters that influence C. parvum oocyst binding to surfaces. Increased understanding of how age and water chemistry influence the binding strength of oocysts may inform future developments in environmental detection and drinking water treatment, such as with the development of oocyst-specific sensors that allow for more frequent tracking of oocysts in the environment. IMPORTANCE The mechanisms by which pathogens bind to surfaces are of interest to a wide variety of scientific communities, as these mechanisms drive infectivity, fate, and transport of the pathogenic organisms. This study begins to reveal the mechanism of direct binding of Cryptosporidium parvum to surfaces containing both carboxylic acid and amine moieties, in an attempt to understand how much of the binding ability is due to long-range electrostatic forces versus other mechanisms (specific or nonspecific) of bonding. In addition to improving the scientific understanding of fate and transport of oocysts, an expanded understanding of the binding mechanisms may aid in the development of new tools and sensors designed to detect and track oocysts in waterways. Furthermore, the methods used to examine binding in this study could be translated to other waterborne pathogens of interest.